Pengaruh Gaya Kepemimpinan Transformasional dan Resonansi Emosional Terhadap Organizational Citizenship Behavior (OCB) Karyawan PT. Tunas Baru Lampung, Tbk Banyu Asin - Fransiska, Septia Bella; Roswaty; Purnamasari, Endah Dewi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This research aims to analyze the influence of transformational leadership style and emotional resonance on employee Organizational Citizenship Behavior (OCB) behavior at PT. Tunas Baru Lampung, Tbk Banyuasin. With a quantitative approach, this research involved 75 respondents consisting of employees in various divisions. The independent variables studied include transformational leadership style and emotional resonance, while the dependent variable is OCB behavior. The research results show that the transformational leadership style partially has no significant effect on OCB, with a t value of 1.306 which is smaller than the t-table of 1.993 (p = 0.196 > 0.05). On the other hand, partial emotional resonance has a significant influence on OCB with a significance value of 0.005 <0.05. Simultaneously, these two independent variables have a significant effect on OCB with a significance of 0.002 <0.05. Regression analysis shows that emotional resonance has a more dominant influence on increasing OCB compared to transformational leadership style, with a regression coefficient of 0.238 and a significance of 0.002 <0.05. The coefficient of determination (R²) of 0.157 indicates that transformational leadership style and emotional resonance together explain 15.7% of the variation in OCB, while the other 84.3% is influenced by other factors. Thus, this research confirms that emotional resonance plays a more dominant influence in increasing employee OCB compared to transformational leadership style.